The Potential of DPSIR Framework to Develop a Holistic Picture of Arctic Industries and Livelihood - A Scoping Review - Moioli, Sara; Tuulentie, Seija; Ólafsdóttir, Rannveig; Siikavuopio, Sten I.; Vacik, Harald; Živojinović, Ivana; Elomina, Jerbelle; Engen, Sigrid; Rautio, Pasi (Artic Institute of North America, 2024)
The Arctic and its resources are becoming a hotspot of increasing political, environmental, and social conflict. The Driver-Pressure-State-Impact-Response (DPSIR) framework can be a useful tool when trying to disentangle the complex issues affecting the region and organize their fundamental components along a causal chain, thus promoting a much-needed integration between social and environmental sciences on one hand and science and policy making on the other (especially when a participatory approach is pursued). The aim of this article is to facilitate and improve future applications of the DPSIR framework in the Arctic context. This is pursued through a comprehensive literature review of the use of the DPSIR framework in the Arctic, with a focus on five of the most important economic sectors in the Arctic economy: aquaculture and fisheries, mining, forestry, tourism, and Indigenous livelihoods. In order to promote the most accurate and balanced approach to the DPSIR framework, its main criticisms and variants are also discussed. The article provides a summary of indicators used in Arctic case studies and focuses on the relevance of the framework as a tool for both local stakeholder involvement and participative policy-making processes. It also provides a general model for application of the DPSIR framework in the Arctic context and, when Arctic examples are not available, a summary of relevant examples outside the Arctic area.
Keywords: stakeholder involvement; interdisciplinarity; indicators; socio-environmental sustainability; fisheries; mining; forestry; tourism; Indigenous livelihoods